Strategi Pemasaran Berbasis Ekonomi Islam dalam Meningkatkan Minat Beli Konsumen: Studi Kasus Toko Sepeda Sinar Surya - Martikawati (Journal Tafkirul Iqtishodiyyah, 2025)
This study aims to examine how Islamic economics views the marketing strategies implemented by Toko Sepeda Sinar Surya. The research contributes to expanding knowledge on marketing strategies used to attract consumer buying interest from an Islamic economic perspective. Data were collected through interviews and documentation, and were analyzed using an inductive qualitative approach. The analysis began with field data related to the application of four marketing strategies; product, price, place, and promotionand was followed by an assessment based on the principles of Islamic economics. The findings indicate that the marketing strategies employed by Toko Sepeda Sinar Surya align with Islamic economic principles. Among the four strategies, the product strategy stands out as a key differentiator: the store provides exclusive service facilities not offered by other bicycle shops in the Metro market. This service feature enhances sales of spare parts, as repair activities often require part replacement, enabling the store to gain dual benefits from service fees and spare part sales